Pengaruh Penerapan Prinsip-Prinsip Good Governance dan Promosi Terhadap Penerimaan Wakaf Tunai (Pada Lembaga Pengelola Wakaf Di Indonesia) - Indri Yuliafitri; Arie Indra Rivaldi (InFestasi, 2017)
Cash waqf is waqf by using cash or money and then the waqf certificate was issued by Islamic financial institutions. The purpose of this research is to determine whether there is an influence of the good governance principles implementation and promotion on receiving of cash waqf fund on the waqf institutions in Indonesia and how the effect of good governance principles implementation and promotion on receiving cash waqf fund on the waqf institutions in Indonesia. The results of the study showed that implementation of the good governance principles have a positive effect but not significant on the receiving cash waqf fund. Promotion have a significant positive effect on receiving of cash waqf fund, then implementation of the good governance principles and promotion simultaneously have a significant positive effect on the receiving cash waqf fund.